Who Gets Monitored among Philippines' 4Ps Children and Why It Matters for Their Nonmonitored Siblings - Michael Ralph M. Abrigo; Kean Norbie F. Alicante; Kris Ann M. Melad (Philippine Institute for Development Studies (PIDS), 2023)
Which children benefit from conditional cash transfers (CCT)? Using a sample of poor and near-poor households in the Philippines, we show that children in households that receive cash transfers from 4Ps, the country's flagship anti-poverty program, have parents with relatively low educational attainment. Within CCT-recipient households, children of heads are more likely to be enrolled for education monitoring. We find no evidence that households select children for education monitoring to maximize 4Ps cash payout. While children's ranking based on birth timing and on an earlier 4Ps prioritization rule predict child monitoring status, these instruments are at best weak, which may effectively limit their use in impact assessments. We confirm earlier findings that 4Ps raise school enrollment on average, which is likely driven by its impact on boys and on older children. We also corroborate earlier results of perverse impacts on non-monitored children that worsens with age, is more severe for boys, and appears to be universal across household compliance types. Contrary to expectations, we show that children in households who select out of 4Ps even when eligible, i.e., never treated, are likely to benefit greatly from the program, while those from households that selects into the program even when ineligible based on proxy means tests, i.e., always treated, are not necessarily better off as a result of the program.
Keywords: 330; poverty; 4Ps; education; marginal treatment effect; Philippines